Unveiling Heavy Metal Pollution in Soils and Rice Crops (Oryza sativa L.) Cultivation - Nana Danapriatna; Moh. Dede; Millary Agung Widiawaty; Hardini Puspitaningrum; Ridwan Lutfiadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The landscape changes through the increasing built-up areas (settlements and industrial) have a potential impact on reducing the quality of agricultural land. Waste from anthropogenic activities (industrial and domestic) is the main source of heavy metals that can affect rice production in the fields. This study examines the quality changes of paddy fields (Oryza sativa L.) polluted by wastewater in Muara Bakti Village, Bekasi Regency. Wastewater's impact on paddy fields is known through heavy metal contamination analysis in soil and rice plants. Chemical analysis of soil, water and plants was completed by the Balai Penelitian Tanaman Sayuran (Balitsa) Laboratory, West Bandung. The results showed that heavy metal levels such as lead (Pb) and cadmium (Cd) in the paddy soil samples were above the threshold in soil, respectively more than 25 mg/l and 0.01 mg/l. In contrast, the rice plant samples, it was identified as containing heavy metals such as Cd and chromium (Cr). Pb content was not detected in the rice plants. Soil in Muara Bakti Village contained optimal nutrients that are still suitable for agriculture. However, heavy metal content detected in soil samples and rice plants requires special handling to prevent endangering the agroecosystem and human health. Keywords: Agroecosystem, Heavy metals, Paddy fields, Soil pollution, Waste